Development Of A Multilayer Scattering Model For Microwave Remote Sensing Of Sea Ice In Antarctica - Albert, Mohan Dass (2007)
In this research, a multilayer model of microwave backscattering is developed based on radiative transfer theory (RT). The RT equation is then solved iteratively. Very often, sea ice is also covered by a layer of snow in Antarctica, therefore in developing our model, snow has been included as one more layer contributing to backscattering coefficient.